Peradilan Agama di Era Orde Baru dan Reformasi Suatu Studi Perbandingan - Malik Ibrahim (UIN Sunan Kalijaga Yogyakarta, 2015)
This paper compared the condition of the Religious Courts in the New Orderwith the Reformation Order, especially the political dynamics in the New Order and thetime of the Reformation and its influence on the condition of the PA in Indonesia. Inhopes of getting the red thread of the results of these comparisons.The approach used inthis paper is the juridical and legal politics in order to test the thesis that the conditionof a democratic society will produce responsive laws or populistic, while the condition ofsociety restrictive laws will produce conservative or orthodox and elitist.As a result of this paper is that the condition of the Religious Courts in theNew Order to Reform Order appears to occur a significant difference, in the NewOrder because the politics are authoritarian, centralized and undemocratic then makethe Religious Courts as the judiciary is not independent and marginalized whencompared with other justice in Indonesia. While in the Era of Reform where the politicsare increasingly democratic and not centralized, the effect on the condition of theReligious Courts are increasingly developed and developing, both from the aspect ofjudicial and non-judicial, especially after the enactment of Law No. 4 of 2004 on thePrinciples of Judicial Power, Law No. 3 of 2006 on Amendments To The Law 7Year 1989 on PA and Law No. 50 Year 2009 concerning the Second Amendmentto Law No. 7 of 1989 on the Religious Courts.